Estudo comparativo da captura híbrida-HPV-DNA por autocoleta domiciliar e coleta médica - Holanda Júnior, Francisco (2005)
Human Papillomavirus infection is the mean cause of the most of cervical cancers. In Ceará this type of cancer is the second in frequency among the women, when the skin cancers are excluded. Cervical cancer is one the most preventable. Where well structured programs exist the mortality has declined, and in some cases in about 80% .The mean problem is that cervical cancer screening is not fully utilized among groups of women, especially those without access or because there are no services offered or when services exist there are many other barriers, since cultural aspects to geographic barriers. In Ceará exist well structured Health communitarian agents program, which we estimate in about 10.000 agents that cover fully the necessities of population in their areas and the all Ceará territory. With this program we can carry on one screening program by self-sampling if this test were acceptable and had a good sensitivity and specificity. By these communitarian agents we could insert in screening program all women who never underwent to pap smear or other type of screening test. The mean objective of this work is to determine whether testing of self-collected vaginal specimen for Human Papillomavirus has the same accuracy of sampling collected by physicians . In order to evaluate this one Cross-sectional observational study was done between August and December of 2002, 878 women from five municipalities were enrolled and the tests were done in the same week, the women started by doing self-sampling at home and after that they were undergone in physician’s clinics to the others examination in following sequence cytology, hybrid capture HPV-DNA, colposcopy and when were necessary biopsy. OF 878 women that participated in this study , 815 were considered negative by the gold standard ,54 were considered positive low grade and 9 were high grade/ carcinoma . Of 878 samples to HPV-DNA , there was negative concordance to both test in 546 samples, there was positive concordance in 216 samples, there was discordance in 35 samples where the physician collect were positive and finally there was discordance in 81 samples where the self-collect were positive. The results of sensitivity to cytology, Hybrid Capture by physicians, Hybrid Capture by self-sampling were, respectively 18%, 63,3% and 66,7%. The prevalence estimated by the gold standard were 7,2% in this sample. The results of specificity to cytology, hybrid capture by physicians, hybrid capture by self-sampling were, respectively 98%, 73% and 68,7%. There was significant difference between the results of HPV-DNA self-collected and collected by the physicians, McNemar test p<0,001. When we compare the concordance through the Kappa index we have obtained k=0,693 with stand error of 0,026. Compared the areas obtained by the ROC curve as follows area=0,738 that represent the achievement of physician collected with IC=[0,673;0,802] with 95% confidence interval to detect HPV in sample, area=0,670 that represent the achievement of self-collected sample to HPV with the 95% of confidence interval IC=[0,597;0,742].We concluded that Hybrid Capture by self-collected vaginal sample is as good as Hybrid Capture collected by the physicians, and there was good concordance between these tests.